2022
DOI: 10.3390/ma15031073
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Thermal Properties of Straw-Based Insulating Panels

Abstract: Cereal straw is an environmentally friendly, rapidly renewable, and sustainable raw material for manufacturing insulating panels for building engineering. Credible data on thermal properties of insulating panels are crucial for appropriate and accurate design of building envelopes. The objective of the study was to determine and validate thermal properties of the panels made of cereal straw. Specific heat was measured with the calorimetric method. Thermal conductivity was determined with the inverse method and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…The thermal performances were quantified using the ISOMET 2114 equipment (Manassas, VA, USA) and consisted of the determination of thermal conductivity [W/mK], thermal diffusivity [m 2 /s], and volume heat capacity [J/m 3 K]. The ISOMET 2114 is a portable measuring instrument designed for the direct measurement of the heat transfer properties of a wide range of isotropic materials, from soils to thermal insulation materials [66][67][68][69][70][71][72][73][74][75][76][77][78][79]. It is possible to equip two types of measurement probes: needle probes for soft materials and surface probes for hard materials.…”
Section: Materials Analysis Methodsmentioning
confidence: 99%
“…The thermal performances were quantified using the ISOMET 2114 equipment (Manassas, VA, USA) and consisted of the determination of thermal conductivity [W/mK], thermal diffusivity [m 2 /s], and volume heat capacity [J/m 3 K]. The ISOMET 2114 is a portable measuring instrument designed for the direct measurement of the heat transfer properties of a wide range of isotropic materials, from soils to thermal insulation materials [66][67][68][69][70][71][72][73][74][75][76][77][78][79]. It is possible to equip two types of measurement probes: needle probes for soft materials and surface probes for hard materials.…”
Section: Materials Analysis Methodsmentioning
confidence: 99%
“…In this work, a transient method was adopted, considering the method reported by Antunes et al [33] and Liuzzi et al [20], as reported in Table 2. The transient method offers several benefits [53,54], in particular the smaller dimension of the testing area. This allowed performing the measurement in different parts of the surface of each sample, indicated in Figure 2a.…”
Section: Methodsmentioning
confidence: 99%
“…The instrument is used to determine the thermal properties of different isotropic materials, including insulating ones, and is widely used in the literature for the determination of the thermal conductivity of building materials [65][66][67][68][69]. The ISOMET 2114 is a commercial portable microprocessor-controlled instrument for direct measurement of the thermal conductivity coefficient of materials and is equipped with two types of measurement probes: a needle probe (for unconsolidated and composite materials) and a surface probe (for solid consolidated and composite materials).…”
Section: Thermal Conductivity Measurementsmentioning
confidence: 99%